Pentingnya Kesehatan Gigi dan Mulut pada Anak Usia Sekolah di RT 10 Kelurahan Murni Kota Jambi - Putri, Vevi Suryenti; Suri, Marta (Universitas Baiturrahim, 2022)
Brushing your teeth is a basic technique for controlling and preventing bacterial infections in the mouth. Brushing teeth is the process of removing dirt and bad breath mechanically from the mouth by using toothpaste and toothpaste and rinsing with clean water (Irma & Intan, 2013). Based on the assessment conducted through interviews, observations and distribution of questionnaires obtained data in RT 10 Kelurahan Murni with a total of 47 households and 172 population, namely school age children 6-12 years have the habit of brushing teeth 1 and 2 times a day 50.0% and the condition of the teeth perforated and black 61.1%. Counseling activities carried out for 45 minutes with the stages of directing participants to the place to be counseling, opening by the moderator, delivering counseling material delivered by the presenter, demonstrating how to brush teeth correctly, distributing leaflets to participants and documenting activities. The results of the counseling of the participants were able to explain again the meaning of brushing their teeth 78.9%, the purpose of brushing their teeth 78.3%, the benefits of brushing their teeth 81.6%, the danger of not brushing their teeth 81.6%, when brushing their teeth 81.6% and their steps step brushing teeth 84.2%.